Case report: Molecular profiling facilitates the diagnosis of a challenging case of lung cancer with choriocarcinoma features - Li, Hui; Hu, Xin; Ning, Matthew S.; Fuller, Gregory N.; Stewart, John M.; Gilliam, Jared C.; Wu, Jia; Le, Xiuning; Vaporciyan, Ara A.; Lee, J. Jack; Gibbons, Don L.; Heymach, John V.; et al. (Frontiers in Oncology, 2024)
Accurate diagnoses are crucial in determining the most effective treatment across different cancers.In challenging cases, morphology-based traditional pathology methods have important limitations, while molecular profiling can provide valuable information to guide clinical decisions. We present a 35-year female with lung cancer with choriocarcinoma features. Her disease involved the right lower lung, brain, and thoracic lymph nodes. The pathology from brain metastasis was reported as "metastatic choriocarcinoma" (a germ cell tumor) by local pathologists. She initiated carboplatin and etoposide, a regimen for choriocarcinoma. Subsequently, her case was assessed by pathologists from an academic cancer center, who gave the diagnosis of "adenocarcinoma with aberrant expression of β-hCG" and finally pathologists at our hospital, who gave the diagnosis of "poorly differentiated carcinoma with choriocarcinoma features". Genomic profiling detected a KRAS G13R mutation and transcriptomics profiling was suggestive of lung origin. The patient was treated with carboplatin/paclitaxel/ipilimumab/nivolumab followed by consolidation radiation therapy. She had no evidence of progression to date, 13 months after the initial presentation. The molecular profiling could facilitate diagnosing of challenging cancer cases. In addition, chemoimmunotherapy and local consolidation radiation therapy may provide promising therapeutic options for patients with lung cancer exhibiting choriocarcinoma features.